Interstitial amino acid concentrations in rodent brain tissue during chemical ischemia. Issue 8 (21st March 2014) - Wölfer, Johannes; Gorji, A.; Speckmann, Erwin‐Josef; Wassmann, Hansdetlef
<x xml:space="preserve">Abstract</x> The significance of electrophysiological phenomena is well validated in brain ischemia research. A close link with interstitial amino acid levels has not been proved convincingly but is generally assumed. This has given widespread rise to the clinical method of amino acid, especially glutamate, microdialysis. We combined microdialytic and electrophysiological techniques in an in vitro ischemia model to test for such a correlation. Rodent hippocampal brain slices were subjected to various patterns of ischemic simulation by depletion of glucose and oxygen and to K+ superfusion, which is often used as an alternative stressor. Our data do not strengthen the significance of clinically standardized glutamate measurements, insofar as ischemia‐induced damage was demonstrated by electrophysiology and histology before being clearly mirrored by interstitial glutamate levels. Taurine would be a more promising candidate. K+ is not an adequate substitute for ischemic simulation, because biochemical and electrophysiological reactions of the tissue are clearly different. In vitro microdialysis during ischemic simulation is feasible and might provide a tool to inquire into glial functions during ischemic stress. It is probably not able to elucidate processes within the synaptic cleft. © 2014 Wiley Periodicals, Inc.